AL-HASHADU POETRY BY AHMAD MATAR (AN ANALYSIS OF RIFFATERRE’S SEMIOTICS) - Umam, Muhammad Choirul; Sakinah, Nyimas (Afshaha: Jurnal Bahasa dan Sastra Arab, 2023)
The language used in poetry is different from the use of language in general. In addition being different in usage, poetry expresses a concept and something indirectly. Language in poetry becomes a sign, which semiotics can be studied to reveal the meaning contained in it. This study examines Ahmad Matar’s poetry entitled “al-Hashadu” by using Riffaterre's semiotic theory. This research is a descriptive qualitative research. The method of data collection applied a documentation by reading and recording techniques. The technique of analyzing data used the heuristic and hermeneutic reading techniques. The results showed that: 1) The heuristic reading of al-Hashadu poetry by Aḥmad Maṭar received imperfect meaning, 2) The hermeneutic reading of al-Hashadu  poetry by Aḥmad Maṭar received a complete meaning structurally, 3) The matrix of al-Hashadu poetry by Aḥmad Maṭar was the resistance to colonialism. The model of the poetry is two sentences in the stanzas "Then there will be one left" and "Truly I am an atheist" and 4) The hypogram of al-Hashadu poetry by Aḥmad Maṭar was the resistance of the Arabs to American colonialism.